Strategic potential of multi-energy system towards carbon neutrality: A forward-looking overview - Tobi Michael Alabi; Favour D. Agbajor; Zaiyue Yang; Lin Lu; Adedayo Johnson Ogungbile (Energy and Built Environment, 2023)
Carbon neutrality is an ambitious goal that has been promulgated to be achieved on or before 2060. However, most of the current energy policies focus more on carbon emission reduction, efficiency and high penetration of renewable energy. Thus, this paper presented a review strategy towards carbon neutrality by presenting the concept of a multi-energy system (MES) in terms of its technologies, configuration, modelling and feasibility as zero-emission equipment. The paper addressed some prominent challenges associated with zero-carbon multi-energy systems (ZCMES). Various proven solutions in the extant studies that have been affirmed to alleviate some of these challenges were presented. In the end, we identified and summarised the current research gaps, and the future directions to ensure the feasibility of ZCMES as a primary strategy towards the actualization of carbon neutrality. Hence, this review work serves as a reference for revising the current energy policies to incorporate a carbon neutrality framework.